The Impact Of The Linguistic Formation On Constructing The Poetic Text An Empirical Study - boulkaaibat, farida (The Notebooks of the Algerian Poetics Laboratory Journal, 2022)
This study investigates the impact of linguistic forms on the construction of the literary text. This imperial study focuses basically on the poetic discourse represented in the poem “Wishayat Nay” by the Algerian poet Abd al-Rahman Bouzarba. The analysis of this poem emphasises on the linguistic aspects (phonemic, morphological, grammatical, semantic ...) described as a set of a linguistic formation of the text to reach coherent and complementary results, because it reflects its linguistic structure. The research used the stylistic approach which is based on the aesthetic, semantic features, and characteristics of the poetic discourse. It is concluded that the poet succeeded to a large extent in the construction of the poetic discourse through building poems on aesthetic language of music, strong words, and style.